The potential of protective glass from smartphones as an emergency personal dosimeter for members of the general public in radiological accidents - SERGEY SHOLOM; Steve McKeever (Brazilian Journal of Radiation Sciences, 2022)
The potential of the back protective glass from modern smartphones as a possible material for an emergency triage, OSL dosimeter was evaluated.  Strong OSL signals were observed in samples of glass from phones of different models and brands after irradiation. Some important parameters of these signals were analyzed, namely the OSL decay curve shape, the dependence on dose, and the stability (fading) with time after exposure. Analysis of the shape suggested that the main mechanism of the OSL production is optically assisted tunneling. The dose-response characteristics demonstrated linearity in the tested dose range (0-2.7 Gy) provided that fading was accounted for during calibration irradiation.   The fading after irradiation was described by a universal, two-component function with a primary component due to tunneling and a secondary, thermal component. Dose reconstruction tests were carried out for in-service phones exposed to known doses and then kept in normal usage (phone calls, texts, web surfing, etc.) as well as for out-of-service phones irradiated to blind (unknown) doses. Dose reconstruction was conducted using a custom-made OSL reader without dismantling any part of the phone. OSL-reconstructed, fading-corrected doses were within 25% (worse case) of the corresponding nominal values. It was concluded that the back protective glass can be used as an OSL emergency triage dosimeter (if protected from ambient light by a phone case).